Pendidikan Keluarga Seimbang yang Melekat Sebagai Basis yang Mencerahkan Anak di Era Digital - Rahmatullah, Azam Syukur (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
The degree of behavioral deviation done by children in the present era is increasingly apprehensive, especially in the digital era which anything seems sophisticated resulting children are "spoiled and pampered" by technological prowess. This is what is called a "digital trapâ, and one of the things that makes it easy for children to get into the trap is due to the "Split Personality" between a child and a parent. In the absence of pure relation and attachment between a child and a parent, consequently, the parents obligation to the child is not fulfilled, one of which is a sincere accompaniment to a child when she or he explores the virtual world through digital media. Therefore, it becomes important that balanced family education is inherent with the child in the home, so that parents more easily lead the child into the positive way while browsing the virtual world through digital media. The parenting patternsought to beapplied based on a strong godliness, open and not manipulative.Ø¥Ù ÙØ³Ø¨Ø© Ø§ÙØØ±Ø§Ù Ø§ÙØ³ÙÙÙÙØ§Øª Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ Ø§ÙØ£Ø·ÙØ§Ù ÙÙ ÙØ°Ø§ Ø§ÙØ¹ØµØ± ÙØ«ÙØ± Ø§ÙÙØ®Ø§ÙÙ. ÙØ®Ø§ØµØ© ÙÙ ÙØ°Ø§ Ø§ÙØ¹ØµØ± (Ø§ÙØ¹ØµØ± Ø§ÙØ±ÙÙÙ) Ø¨ÙØ§ ÙÙÙ ÙÙ Ø§ÙØ£Ø´ÙØ§Ø¡ Ø§ÙØ±Ø§ÙÙØ©Ø Ø¬Ø¹Ù Ø§ÙØ£ÙÙØ§Ø¯ ÙÙØ¯ÙÙÙÙÙ ÙÙÙ Ø¨ØªÙØ¯Ù Ø§ÙØªÙÙÙØ©. ÙÙØ°Ø§ ÙÙ Ø§ÙÙØ³ÙÙÙ Ø¨Ø§ÙÙØ®Ø§Ø® Ø§ÙØ±ÙÙÙØ ÙØ£ØØ¯ Ø§ÙØ£Ø³Ø¨Ø§Ø¨ ÙÙ Ø³ÙÙÙØ© Ø§ÙØ£Ø·ÙØ§Ù ÙÙØ¯Ø®ÙÙ ÙÙ Ø§ÙÙØ®Ø§Ø® Ø§ÙØ±ÙÙÙ ÙÙ ÙØ¬ÙØ¯Â  Ø§ÙÙØµØ§Ù Ø§ÙØ´Ø®ØµÙØ© Ø¨ÙÙ Ø§ÙØ£ÙÙØ§Ø¯ ÙØ§ÙÙØ§ÙØ¯ÙÙ. ÙØ¨Ø¹Ø¯Ù Ø§ÙÙØ±Ø¨ Ø§ÙØ®Ø§ÙØµ Ø¨ÙÙ Ø§ÙØ£ÙÙØ§Ø¯ ÙØ§ÙÙØ§ÙØ¯ÙÙ ÙØ§ ÙØ³ØªÙÙÙ Ø£Ø¯Ø§Ø¡ ÙØ§Ø¬Ø¨Ø§Øª Ø§ÙÙØ§ÙØ¯ÙÙ ØªØ¬Ø§Ù Ø§ÙØ£ÙÙØ§Ø¯Ø ÙÙÙÙØ§ ÙØµØ§ØØ¨Ø© Ø®Ø§ÙØµØ© ÙØÙ Ø§ÙØ£Ø¨ÙØ§Ø¡ ØÙÙ ØºØ§ØµÙØ§ ÙÙ Ø§ÙÙØ¶Ø§Ø¡ Ø§ÙØ¥ÙÙØªØ±ÙÙÙ Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØ¬ÙØ§Ø² Ø§ÙØ±ÙÙÙØ ÙØ°Ø§ ÙØ¥Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ£Ø³Ø±ÙØ© Ø§ÙÙØªÙØ²ÙØ© ÙÙÙØ© ÙÙØ£ÙÙØ§Ø¯ ÙÙ Ø§ÙØ¨ÙØªØ ÙÙØ³ÙÙ ÙÙØ¢Ø¨Ø§Ø¡ ØªÙØ¬ÙÙ Ø§ÙØ£ÙÙØ§Ø¯ Ø¥ÙÙ Ø§ÙØ·Ø±ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¥ÙØ¬Ø§Ø¨ÙÙ Ø·ÙØ§Ù ØºÙØµ ÙØ¤ÙØ§Ø¡ ÙÙ Ø§ÙÙØ¶Ø§Ø¡ Ø§ÙØ¥ÙÙØªØ±ÙÙÙ. ÙØ£Ø³ÙÙØ¨ ØªØØ¶ÙÙ Ø§ÙØ£ÙÙØ§Ø¯ Ø§ÙØ°Ù ÙÙÙÙ ÙÙÙØ§ÙØ¯ÙÙ Ø§ØªÙØ®Ø§Ø°Ù ÙÙ Ø§ÙØ£Ø³ÙÙØ¨ Ø§ÙÙÙÙÙ Ø§ÙÙØ¤Ø³ÙØ³ Ø¹ÙÙ Ø§ÙØ¯ÙÙØ ÙØ§ÙÙØªÙØªÙØ ÙÙØ§ Ø®Ø¯Ø§Ø¹ ÙÙÙ.Â